2021
DOI: 10.3390/jcm10061297
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pelvic Circumferential Compression Devices in Pelvic Ring Fractures—Are Guidelines Followed in Daily Practice?

Abstract: Early administration of a pelvic circumferential compression device (PCCD) is recommended for suspected pelvic trauma. This study was conducted to evaluate the prevalence of PCCD in patients with pelvic fractures assigned to the resuscitation room (RR) of a Level I trauma center. Furthermore, correct application of the PCCD as well as associated injuries with potential clinical sequelae were assessed. All patients with pelvic fractures assigned to the RR of a level one trauma center between 2016 and 2017 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Furthermore, pelvic binders are supposed to be an integral part of the preclinical phase, similar to routine C-spine immobilization for suspected cervical trauma [7,37,40,[45][46][47]. However, application may not be effective in patients with vertical shear type fractures, concomitant proximal femur, or acetabular fractures (60% in the present study and 1.5% of pelvic fractures requiring emergency external stabilization [7]) and carries a risk of overreduction, misplacement, and pressure sores after 24-36 h [45,[48][49][50]. In the context of the interregional variation of preferences and algorithms [14,26,40,51], the clarification of the resuscitative potential of C-clamps within the cascade of emergency management is essential.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, pelvic binders are supposed to be an integral part of the preclinical phase, similar to routine C-spine immobilization for suspected cervical trauma [7,37,40,[45][46][47]. However, application may not be effective in patients with vertical shear type fractures, concomitant proximal femur, or acetabular fractures (60% in the present study and 1.5% of pelvic fractures requiring emergency external stabilization [7]) and carries a risk of overreduction, misplacement, and pressure sores after 24-36 h [45,[48][49][50]. In the context of the interregional variation of preferences and algorithms [14,26,40,51], the clarification of the resuscitative potential of C-clamps within the cascade of emergency management is essential.…”
Section: Discussionmentioning
confidence: 96%
“…A study of inhospital and prehospital pelvic compression device use at U.S. Level I trauma centers found that prehospital pelvic compression devices were not applied to all suspected pelvic fractures (Jarvis et al, 2020). Similarly, Kuner found that only one-third of patients with pelvic fractures assigned to the resuscitation room of a Level I trauma center had a pelvic compression device applied (Kuner et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kuner, the position of the pelvic compression devices was assessed on the computed tomographic scan and rated as incorrect if the pelvic compression device did not cover the greater trochanters (Kuner et al, 2021). They found that 39% of pelvic compression devices were positioned incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…29,41,48 Due to the pressure on skin that may be traumatized, pelvic binders and pelvic binders should not remain in place for longer than a few hours. 49,50 Clinical Question 11: What Are the Indications for Conservative Treatment of FFPs in the Elderly? Recommendation 11: Conservative treatment is suitable for patients with type I and II but dynamic assessment is required (Grade of evidence and recommendation: 2B).…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Due to the mechanisms of injuries, features of fractures, OP, pelvic C‐clamp and external fixation or emergent angiograph are technically more difficult than applying a pelvic sheet or binder in patients of FFP, and serious complications have been described in several publications 29,41,48 . Due to the pressure on skin that may be traumatized, pelvic binders and pelvic binders should not remain in place for longer than a few hours 49,50 …”
Section: Clinical Questionsmentioning
confidence: 99%